DEVELOPING A WORKBOOK OF BASIC LISTENING COURSE FOR THE THIRD SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT IAIN ANTASARI BANJARMASIN - Hidayah Nor; Nur Alfa Rahmah (Universitas Islam Negeri Walisongo Semarang, 2015)
Work book is one of the principal necessities in the processof teaching and learning second language. A comprehensive work-book will work as step-by-step guidance both for the teacher andstudents; teacher will know what to do to transfer the knowledgeeffectively within very limited time constraint; and students will beprovided clear clue to comprehend required materials and acquirethe necessary skills. Without work book, teacher will have to thinkand work harder in every meeting to measure their students’ needsand adapt the materials to their comprehension capacity.Third semester students of English Teaching Department ofIAIN Antasari Banjarmasin can be classifi ed as beginning learnersof English. For most students who live in a non-speaking Englishcountry such as Indonesia, listening skill is diffi cult to comprehend.Listening skills is seen not only as something valuable for itsown sake but as something that supports the growth of other as-pects of language use, such as speaking and reading. The assump-tions of teaching listening as comprehension are: listening servesthe goal of extracting meaning from messages, the learners have to be taught how to use both bottom up and top down processes inarriving at an understanding of messages, and the language of ut-terances used by speakers are temporary carriers of meaning. Oncemeaning has been identifi ed there is no further need to attend to theform of messages.Students have problems to catch the actual sounds of the for-eign language; understand every word which make them feel wor-ried and stressed; understand fast, natural native-sounding speech;keep up with all the information they get and they cannot predict.To overcome these problems teachers can help students by teachthem how to improve their listening through some skills and teachthe students by using media.Dealing with the purpose of this research in developing work-book for English listening class, the suitable design for this researchis research and development (RD).